Body composition in sport, exercise, and health - Stewart, Arthur D.; Sutton, Laura (Routledge, 2012)
The analysis of body composition (fat, bone and muscle) is an important process throughout the biomedical sciences. This is the first book to offer a clear and detailed introduction to the key methods and techniques in body composition analysis and to explain the importance of body composition data in the context of sport, exercise and health. With contributions from some of the world's leading body composition specialists, the book goes further than any other in demonstrating the practical and applied value of body composition analysis in areas such as performance sport and weight control in clinical populations. The book pays particular attention to the important concept of change in body composition, and includes discussion of ethical issues in the collection, interpretation and presentation of data, and considerations when working with special populations. Bridging the gap between research methods and practical application, this book is important reading for advanced students and practitioners working in sport and exercise science, health science, anatomy, nutrition, physical therapy or ergonomics.